Guzhi Zengsheng Zhitongwan, a Traditional Chinese Medicinal Formulation, Stimulates Chondrocyte Proliferation through Control of Multiple Genes Involved in Chondrocyte Proliferation and Differentiation. (12th September 2018) - Yao, Baojin; Lu, Bocheng; Gao, Hongwei; Zhang, Mei; Leng, Xiangyang; Zhao, Daqing
Abstract : Chinese materia medica (CMM) are essential components of traditional Chinese medicine, and Chinese medicinal formulas consisting of 2 or more types of CMM are widely used. These formulations have played a pivotal role in health protection and disease control for thousands of years. Guzhi Zengsheng Zhitongwan (GZZSZTW), which represents one of the Chinese medicinal formulations, has been used for several decades to treat joint diseases. However, the exact molecular mechanism underlying its efficacy in treating osteoarthritis remains to be elucidated. In the present study, we investigated the effects of GZZSZTW on primary chondrocytes. We demonstrated that GZZSZTW significantly promoted chondrocyte viability, maintained chondrocytes in a continuous proliferative state, and prevented their further differentiation. These effects were achieved by the synergistic interactions of various herbs and their active components in GZZSZTW through an increase in the expression levels of functional genes participating in chondrocyte commitment and proliferation and a decrease in the expression levels of genes involved in chondrocyte differentiation. GZZSZTW treatment also decreased the expression levels of genes that inhibited chondrocyte proliferation. Thus, this study has greatly deepened the current knowledge about the molecular effects of GZZSZTW on chondrocytes. It has also shed new light on possible strategies to further prevent and treat cartilage-related diseases by using traditional Chinese medicinal formulations.